Rancang Bangun Pembangkit Listrik Termoelektrik dengan Menggunakan Limbah Tongkol Jagung - Aldiansyah, Satria; Djohar, Abdul; ., Asminar (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
The large amount of corn cob waste that has not been optimally utilized is one of the challenges in the agricultural sector, although this waste has the potential to become an economically valuable and environmentally friendly biomass energy source. The increasing demand for electricity, which is not matched by fossil fuel availability, is also encouraging the development of sustainable alternative energy sources, especially those derived from local agricultural waste. Therefore, this study aims to design and analyze the performance of a thermoelectric power plant utilizing corn cob waste to meet daily electricity needs and evaluate its potential as a small-scale alternative energy source. The methods used include prototype design, system assembly using Peltier modules arranged in series-parallel, a biomass combustion system, a water-circulation cooling system, and testing based on voltage, current, power, and temperature difference (ΔT) parameters. Test data were collected periodically during combustion to determine the system output characteristics. The results show that the use of 9 Peltier modules with 2 kg of corn cobs as fuel produces a maximum power of 8.192 W with a current of 0.64 A under the highest temperature difference conditions. The prototype test results were then used as the basis for a simulation to estimate system development, where an output energy of 1040 Wh requires 16 combinations or 144 Peltier units operating for 8 hours using approximately 16 kilograms of corn cobs as fuel.